Vascular-targeted photodynamic therapy: a glimpse in the future of Urology? - Kallidonis, Panagiotis; Liatsikos, Evangelos N. (Translational Cancer Research, 2017)
The technological development and the continuous research in the field of prostate cancer (PCa) have not overcome significant clinical questions and ethical dilemmas related to the treatment of the disease. Current efforts to provide recommendations in the optimal treatment of PCa patients has provided significant standardization of the current knowledge and eventually produced guidelines which are widely acceptable. Nevertheless, a plethora of clinical issues commonly met in the everyday clinical practice such as the optimal management of low risk prostate cancer patients remain inadequately addressed by the literature (1,2). These patients are considered to have a low risk for disease progression and their management by radical approaches may expose them to risk of significant morbidity. In an attempt to optimize the care of this PCa population, different approaches have been proposed (2).